(-8f)*(-f+8)=0

Simple and best practice solution for (-8f)*(-f+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-8f)*(-f+8)=0 equation:



(-8f)(-f+8)=0
We add all the numbers together, and all the variables
(-8f)(-1f+8)=0
We multiply parentheses ..
(+8f^2-64f)=0
We get rid of parentheses
8f^2-64f=0
a = 8; b = -64; c = 0;
Δ = b2-4ac
Δ = -642-4·8·0
Δ = 4096
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4096}=64$
$f_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-64)-64}{2*8}=\frac{0}{16} =0 $
$f_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-64)+64}{2*8}=\frac{128}{16} =8 $

See similar equations:

| 2u-u+3=15 | | 2(3x+4)-3x=3(x+8) | | 4(n+1)-3=13 | | -1/3x+5=-2+5/7x | | 198=97+x | | 90=(7+2x)+(4x) | | (-s-5)+(-2s+2)=0 | | -10=-9z+10 | | 19-8c=11c-2+9 | | -10=-9z+1= | | x÷-1/6=21 | | 43=w/4+14 | | 234=97+a | | 3(4w+3)=-4 | | 2X+14x-16=3x+40 | | 5(1+k)=-9k+6 | | 9*k=6*k-7 | | -10-6k=-2k-18 | | 24=-11y-8-3y | | (12y+12)=180 | | 7x-5=4x-5 | | 5(1+5k)=-9k+6 | | -5n+10=-6n-6 | | 450=150+30m | | -10.87+5m=7.4m-2.42+18.43 | | (r÷4)−3=7 | | (13x-25)=(9x-1) | | -8-3n=4 | | 13x-25)=(9x-1) | | 30=450+150m | | -3(x+2=-12 | | x+x-10+.90=180 |

Equations solver categories